2014
DOI: 10.1093/humrep/deu149
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a duplication within the GDF9 gene and novel candidate genes for primary ovarian insufficiency (POI) by a customized high-resolution array comparative genomic hybridization platform

Abstract: STUDY QUESTIONCan high-resolution array comparative genomic hybridization (CGH) analysis of DNA samples from women with primary ovarian insufficiency (POI) improve the diagnosis of the condition and identify novel candidate genes for POI?SUMMARY ANSWERA mutation affecting the regulatory region of growth differentiation factor 9 (GDF9) was identified for the first time together with several novel candidate genes for POI.WHAT IS KNOWN ALREADYMost patients with POI do not receive a molecular diagnosis despite a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 46 publications
0
33
0
2
Order By: Relevance
“…A possible hint comes from a recent study that found co-occurrence of a large deletion in the human DNAH6 locus and primary ovarian insufficiency. 51 The high rate of amino acid substitutions during mammalian evolution of the DNAH6 mutated amino acid region might be mainly due to adaptive selection, a feature highly associated with some genes involved in reproduction. [52][53][54] Notably, dynein genes have been suggested as the main components of the force generating rapid prophase movements of the chromosomes (RPMs) during meiosis in various phylogenetic classes.…”
Section: Discussionmentioning
confidence: 99%
“…A possible hint comes from a recent study that found co-occurrence of a large deletion in the human DNAH6 locus and primary ovarian insufficiency. 51 The high rate of amino acid substitutions during mammalian evolution of the DNAH6 mutated amino acid region might be mainly due to adaptive selection, a feature highly associated with some genes involved in reproduction. [52][53][54] Notably, dynein genes have been suggested as the main components of the force generating rapid prophase movements of the chromosomes (RPMs) during meiosis in various phylogenetic classes.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a large number of genes or genomic loci, affected by common CNVs or single nucleotide polymorphisms (SNPs) and identified by genome-wide association studied (GWA), may have a role in the disease susceptibility but can explain only a small proportion of the total heritability of POI (23). The analysis of a few cohorts of 46,XX POI patients by means of high throughput techniques, such as comparative genomic hybridization array (array-CGH) and SNP array, has led to the identification of CNVs affecting several X-linked and autosomal loci with a possible role in female fertility (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). Similarly, the recent application of whole-exome sequencing (WES) to a few POI multigenerational familial cases has succeeded in revealing rare single nucleotide variants affecting genes implicated in ovarian function (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48).…”
Section: The Heterogeneous Manifestations and Multifactorial Origin Omentioning
confidence: 99%
“…In addition, the elevated frequencies of certain GDF-9 heterozygous variants, including the C447T SNP, have been identified in European, Caucasian and Asian women with POF failure (26,28,37,38), however, not in New Zealander or Japanese woman (27,38). A tandem duplication of 475 bp in the GDF-9 promoter was previously identified as a causative factor of primary ovarian insufficiency (39). The GDF-9 variants have also been associated with the risk of PCOS (40) and have been associated with hirsutism scores and parity in patients with PCOS (41).…”
Section: Discussionmentioning
confidence: 99%